2022
DOI: 10.1039/d2gc01248k
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst- and oxidant-free electrooxidative site-selective [3/4 + 2] annulation to fused polycyclic heteroaromatics

Abstract: Annulation π-extension of arenes with alkynes is a straightforward and practical strategy for the rapid construction of polycyclic aromatic compounds. Recently, some intriguingly transition-metal-catalyzed polycyclic arene syntheses were described. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The result revealed that 1 might be firstly oxidized and then underwent radical addition with 2 , which was similar to our previous study. 15 And, the oxidative potentials of intermediates 35 and 36 were found 1.27 V and 1.13 V, which indicated that 1 reacted with 2 to form an intermediate with a lower oxidation potential, which was further oxidized (Fig. 2).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The result revealed that 1 might be firstly oxidized and then underwent radical addition with 2 , which was similar to our previous study. 15 And, the oxidative potentials of intermediates 35 and 36 were found 1.27 V and 1.13 V, which indicated that 1 reacted with 2 to form an intermediate with a lower oxidation potential, which was further oxidized (Fig. 2).…”
mentioning
confidence: 91%
“…Recently, a straightforward and practical electrochemical synthesis strategy for the production of fused polycyclic heteroaromatic compounds through annulative π-extension of unfunctionalized arenes with alkynes was reported by us. 15 These fused polycyclic heteroaromatic compounds with π-conjugated systems have excellent photoelectric properties and have extensive application prospects in many fields. 3 c ,16 With our continued interest in electrochemical oxidative cross-coupling with hydrogen evolution, some electrochemical coupling reactions to construct new C–C 17 bonds have been previously reported by us.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As an efficient, mild, eco-friendly method, organic electrochemical synthesis offers a directed oxidative route for organic substrates under oxidant-free conditions and has received continuous attention. Organic electrochemical synthesis has been utilized to achieve the C-H activation/annulation, [22][23][24][25] the construction of polycyclic aza-fused arenes [26][27][28][29] and polycyclic S-containing arenes, 30 and the electrochemical transformation of phosphorus compounds have also been reported. [31][32][33] With our continuous interests in electrochemistry [34][35][36][37][38][39] and multiple C-H activations and annulation 19,40 , herein, we report a versatile electrochemical oxidative method under oxidant-free conditions to produce fused polycyclic phosphonium salts via the C-H activation/annulation of aryl phosphine compounds (Scheme 1d), and metals and oxidants could be readily avoided in this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that electrochemically promoted metal-free procedures might also be feasible through a radical pathway. The key features of such an annulation protocol are (1) the excellent control of regioselectivity in terms of the asymmetric internal alkyne, (2) metal- and chemical-oxidant-free conditions, and (3) the tolerance of various functional groups (Scheme c) …”
mentioning
confidence: 99%